2021
DOI: 10.1111/trf.16369
|View full text |Cite
|
Sign up to set email alerts
|

A national level estimation of population need for blood in India

Abstract: Background The population need for blood is the total volume required to transfuse all the individuals who need transfusion in a defined population over a defined period. The clinical demand will arise when people with a disease or condition who require transfusion, access healthcare services, and subsequently the clinicians request blood. Essentially, the conversion of need to demand must be maximum to avoid preventable mortality and morbidity. The study estimated the population need for blood in India. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…9 Moreover, recent modelling studies have shown that the previously proposed donation target rate of 10–20 units per 1000 people is an underestimate of actual need. 10 However, no studies have captured the true need where transfusion services are the most inaccessible. The only metrics assessing access are based on political borders and not geographical constraints.…”
Section: Resultsmentioning
confidence: 99%
“…9 Moreover, recent modelling studies have shown that the previously proposed donation target rate of 10–20 units per 1000 people is an underestimate of actual need. 10 However, no studies have captured the true need where transfusion services are the most inaccessible. The only metrics assessing access are based on political borders and not geographical constraints.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for deferring a likely donor is to safeguard the health of the donor as well as the patient. The annual rate of blood donations in India is 7.4 million units whereas the demand is 10 million [1] .it is clearly evident there is always a shortage of blood at any given point of time [2] . This shortage of demand could be narrowed by strictly following the donor selection criteria and avoiding the unnecessary deferrals.…”
Section: Introductionmentioning
confidence: 99%
“…A Mumbai-based survey showed that the incidence is 1: 7,600 in Mumbai city to 1: 2,500 in certain parts of Maharashtra ( Agarwal et al, 2016 ). In India, the medical need accounted for 41.8% of blood requests followed by surgery (25.3%), pediatrics (19.0%), and obstetrics (13.8%) ( Mammen et al, 2021 ). But clinical guidelines often overlook the critical aspects of managing patients with unique blood groups.…”
Section: Introductionmentioning
confidence: 99%